ArcView GIS Demo Edition February 1999 (USA ESRI Inc., 1992)
A Multimedia GIS Tuor on this CD tells you about ArcView GIS, other software from ESRI, map data, and GIS solutions
Title on booklet cover
System requirement : on booklet cover
Keywords: GIS ArcView -- Demo Edition